Tuber Yield and Economics of Potato as Affected by Application of Vermicompost, Mineral Nitrogen and Phosphorus in Southwestern Ethiopia - Isreal Zewide; Sanjay Singh; Henok Kassa (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Multi-nutrients deficiency of soil in southwest Ethiopia is among the primary constraints for the very low productivity of potatoes (Solanum tuberosum L.). The combined use of organic and inorganic fertilizers is vital for resolving the common productivity issue. Thus, experiments were performed on potato variety â€œBelteâ€ in Masha district, southwestern Ethiopia, in both Belg (February to May) as well as Meher (June to October) seasons of 2019 to evaluate the potato response to the vermicompost, mineral phosphorus, and nitrogenâ€™s integrated applications. The experiment had three vermicompost rates with the factorial combination (2.5, 5, 7.5 t/ha) and three recommended rates inorganic NPâ€™s 25%, 50% and 75% (124 kg N/ha and 103 kg P2O5/ha) fertilizer. Results have discovered that 75% inorganic NP and 7.5 t/ha vermicompostâ€™s combined application significantly increase total tuber yield, marketable tuber yield, and individual tuber weight, giving the maximum net benefits and marginal return rate. Thus, it has been discovered from this work that for potato production at Masha area, 7.5 t/ha vermicompost with inorganic NPâ€™s 75% recommended doseâ€™s combined applications are best-integrated nutrient management options.